A study of Indian Pentecostal Church membership with reference to a model of religious change - Buijs, Georgina Cicely Vauriol (Department of Religious Studies, 2023)
This thesis is a socio-historical account of the founding and development of the largest Christian denomination among South African Indians - Bethesda, or the Indian branch of the Full Gospel Church of Southern Africa, with reference to a model religious belonging and change developed by Professor J.S. Cumpsty. The members of Bethesda are drawn largely from the descendants of Tamil and Telegu speaking indentured labourers who were brought to South Africa mainly to work in the sugar plantations of Natal in the latter half of the nineteenth century. The early chapters of the thesis examine the background of these people, including the circumstances surrounding their emigration from India, most often due to famine, and the harsh conditions they endured on the estates in Natal in the early years of indenture. The religion the indentured brought with them to Natal was the 1 folk 1 Hinduism of their native Indian villages where worship often centred around local deities who needed to be propitiated to prevent outbreaks of epidemic diseases. This religion conformed to what Cumpsty has called 1Nature Religion 1 in which immediate experience is conceived of as real, reality as monistic and time as cyclical (biological). It is corporate, present texture of life oriented and largely a behaviour pattern. Religious knowledge is typically wisdom. Although some effort was made to convert Indians to Christianity at this time, notably by Methodist and Anglican missionaries, little success was achieved and Christianity remained for Indians in South Africa a 'white man's religion 1. Later chapters in the thesis show that by the nineteen twenties, however, the socio-cultural experience of the Indians had changed. Few then remained in agricultural work, most were employed in unskilled or semi-skilled positions in manufacturing industries or service positions in the rapidly growing urban areas. It was at this time that Bethesda was founded as the United Pentecostal Mission in Pietermaritzburg by J.A. Rowlands and Ebenezer Theophilus. Although the appeal of Pentecostalism was limited among Indians initially, and there is some evidence that early Christian converts were ostracised by their relatives, when J.F. Rowlands, the elder son of J.A. Rowlands, moved to Durban and founded Bethesda, within a few years the church succeeded in becoming well established in Durban and surrounding areas of Natal. This phase in the history of Bethesda may be correlated with what Cumpsty, in terms of his model of religious belonging, has called the Irrational or Paradoxical Stage. In this stage religious beliefs gain their authority from their success in creating the required sense of belonging because they are independent of the chaotic or unacceptable socio-cultural experience. In this paradoxical stage the highly emotionally charged religious meeting, charismatic experience and charismatic figure find their place, as Rowlands provided with his revival campaigns, 1Bethesdascopes 1 , 'Musical Sermons' and the puritanical life style and ethic enjoined in his teachings. By the sixties the chaotic life experience of South African Indians has stabilized. Increasing levels of education for young people and expectations of a better life than their parents had led were reflected in a new emphasis in Bethesda on theological training, dignity and order in both worship and the appearance of church buildings. Thus the members of Bethesda sought to enter an Integrative stage where beliefs and practices had to be relevant to the socio-cultural experience. By the nineteen eighties, and consequent on the death of J.F. Rowlands and closer links with other Full Gospel churches in South Africa, Bethesda has clearly moved away from being an Indian Christian church to an emphasis on_ a wider humanitarian concern in which Indian identity is subsumed under a Pentecostal umbrella which includes missionary activity overseas and links with Pentecostal churches in the United States. The success of Bethesda, in contrast to the relative failure of other Christian denominations among Indians in South Africa, can be clearly seen in its ability not only to provide a sense of belonging in changing sociocultural experiences but to actively promote the aims and aspirations of its members in a rapidly changing world.